Evaluación de los procesos de pretratamiento requeridos para el tratamiento biológico de los residuos de aceites usados de motor diésel (2019)
he project, which is carried out with the support of the research group in Alternative Energies of the Universidad de América in conjunction with the Centro de Tecnologías del Transporte (CTT) of Sena. Throughout its useful life, motor oils lose their properties due to the appearance of contaminants and impurities resulting from undesirable oxidation processes. Used lubricating oil of diesel engine was characterized in order to establish its contaminants, through the use of analytical techniques and reduce its toxicity through the application of physicochemical pretreatments, providing an environmental solution as an alternative for the use of waste oils from the automotive industry . The diesel engine lubricant oil from the Centro de Tecnologías del Transporte was characterized physicochemically, in this parameters were determined as viscosity, density, pH, TBN, TAN and wear elements. From the physicochemical characterization of the oil under study, it has a viscosity at 100 ° C of 6.2 cSt, a density of 0.87 g / ml, a pH of 6.82, total basic number (TBN) of 6, 0 mgKOH / g and total acid number (TAN) of 2.15 mgKOH / g. Similarly, high levels of water and contaminants such as iron, aluminum, silicon, sodium and copper were found. The treatments selected to treat the used oil are acidification with sulfuric acid and adsorption. For the acidification, the percentage of sulfuric acid is varied (5%, 10% and 15%) and for the adsorption treatment activated carbon and ilmenite were chosen as adsorbent